The Importance of Insects in Australian Aboriginal Society: A Dictionary Survey - Si, Aung; Turpin, Myfany (Ethnobiology Letters, 2015)
Insects and their products have long been used in Indigenous Australian societies as food, medicine and construction material, and given prominent roles in myths, traditional songs and ceremonies. However, much of the available information on the uses of insects in Australia remains anecdotal. In this essay, we review published dictionaries of Aboriginal languages spoken in many parts of Australia, to provide an overview of the Indigenous names and knowledge of insects and their products. We find that that native honeybees and insect larvae (particularly of Lepidoptera and Coleoptera) are the most highly prized insects, and should be recognized as cultural keystone species. Many insects mentioned in dictionaries lack scientific identifications, however, and we urge documentary linguists to address this important issue.